Animal advocate. (13th September 2014) - Knight, Andrew
Abstract : Andrew Knight is a European veterinary specialist in animal welfare science, ethics and law who speaks regularly on animal welfare issues at universities and conferences internationally. Here, he describes how his career has developed, along with his interest in cryptozoology